Solidão a pino - Bortulini, Gabriel Eduardo (2017)
This master’s thesis is composed of two parts: a short stories collection and an essay that analyses my own creative process. The project emerges from a synesthetic perception: monotonous and wavy, the milonga rhythm seems to synthetize the South American pampas - its place of origin. But could only the milonga cause this feeling? What would be this synthesis transposed to literature? The question comes from the reading of an essay named A estética do frio, wrote by Vitor Ramil (2004). For the author, the cold weather is the distinct element between the “esthetic” of tropical Brazil and the cold one from the pampas’ social imaginary. But, besides cold, isn’t there any other element? Hidden in the gaucho’s imaginary, wouldn’t there be another condition? The solitude – this “ultimate depth of human condition”, according to Octavio Paz (1984) – defines and unites the gaucho to the world. By this hypothesis, the project proposes a literary work influenced by the geographical space.